Establishing codes from exemplary teachers’ practice in preparing teachers for character education / Loo Yee Ling - Loo, Yee Ling (2016)

(untitled)
There is no clear understanding on what constitutes exemplary practices in a situated classroom teaching for character education. The important purpose of this study was to scrutinize how a novice teacher could be guided by an exemplary teacher for character education through the infusion of the established codes. The study was divided into two aspects, namely the establishment of codes of exemplary teachers’ practice and infusing these codes in preparing novice teachers for character education at a selected institution. This study was carried out in three phases. The phases were planned and executed based upon three objectives which were, (i) Phase 1 - Situated Classroom Observations (SCO) and Exemplary Teacher Interviews (ETI) were utilised to explore the situated knowledge of an institution’s (Prokidz) exemplary teachers in the context of classroom teaching practice in relation to character education; (ii) Phase 2 - establish the codes of exemplary situated teaching for character education grounded in the data collected from exemplary teachers in Phase One (iii) Phase 3 - identify the factors that affect ‘learning to teach’ experiences of the novice teachers using the established codes at the Institution through Novice Teacher Interviews (NTI). The emerging codes of exemplary situated teaching dispositions and practices for character education was named as the CRAMVIL Mode of Teaching. CRAMVIL is an abbreviation for ‘Creativity’, ‘Relationship’, ‘Assessment’, ‘Motivation’, ‘Value’, ‘Instruction’, and ‘Linkage’. Overall, The CRAMVIL Mode of Teaching which emerged from the extensive data has seven teaching codes that branch out into twelve iv components and further branch out into thirty-two elements. The presentation of the codes include four aspects namely, (i) description of the code (ii) teachers’ roles and practices (iii) real life example of practices and dispositions (iv) indicators from students’ actions and behaviours in class. The established codes in this study included all four aspects to illustrate a more comprehensively written guideline to facilitate the novice teacher’s understanding to be an exemplary character educator. The uniqueness of these codes is established through a situated classroom setting of character education quoted with real life examples that are exemplified by exemplary teachers at the Institution. From this study, several factors that affect the ‘learning to teach experience’ of novice teachers were elucidated. Novice teachers learn through an active learning approach in a situated classroom setting where there is an avenue for them to learn and apply with the help of an exemplary teacher’s (coach) guidance. The guidance comes with feedback as they are aware of their strength and weakness from an expert’s point of view, hence improving gradually and periodically maximizing teaching skills. It was found that ‘modelling’, ‘articulation’ and ‘journaling’ are learning tools to enhance novice teachers’ situational teaching knowledge and skills. Both novice teachers admired and liked their coaches very much as they were caring, and supportive and constantly gave them encouragement as well as motivation throughout the learning process. They appreciated the interpersonal relationship and agreed that their learning experience was happy and fruitful. Implications of the findings and suggestions for further research are also discussed.